Effectiveness of mini- clinical evaluation exercise (mini cex) in assessment of physiotherapy students - DR. MANISHA RATHI,; PREETI GAZBARE, (International Journal of Pharma and Bio Sciences, 2017)
Traditional pattern of assessment is lacking in uniformity, time constraint, and is bias. The mini-clinical evaluation exercise (mini-CEX) is widely used for assessment in single work-based encounters of clinical competence. Drawbacks of traditional method can overcome by using this technique. But it is not used in physiotherapy education. To assess effectiveness of Mini-CEX pattern of assessment in evaluating Physiotherapy undergraduate students. The study was conducted in Dr. D. Y. Patil College of Physiotherapy, Pune on 20 Final year physiotherapy students. Students were evaluated by 12 teachers using Mini CEX assessment Performa. Students were evaluated case in given time and examiner observed them while evaluating the patient silently. After assessment, feedback was taken regarding the effectives of this pattern. All students and 83.33% teachers accepted that Mini CEX is more objective pattern of assessment than traditional one. Students (80%) and Teachers (58.33%) felt that it should be the ideal pattern of examination in the physiotherapy curriculum. Students (90%) and 83.33% teachers accepts that this pattern assess the student thoroughly. Both students (85%) and teachers (91.67%) agreed that overall it is very effective way of assessment of student. This study concluded that Mini CEX was well accepted by the students and teachers and it is feasible to introduce in the physiotherapy examination provided time allotted for diagnosing the case was sufficient. However, further studies are required before implementation of Mini CEX in university examination.